(untitled) (Web of Teachers: Inderscience Research, 2025)
Tooth extraction mouth from the void pathological changed, healed impossible or purulent infection source become remaining tooth surgery way with take throw Extraction mainly tooth root deep caries as a result erosion, periodontitis, periostitis or osteomyelitis such as purulent processes appearance to be in cases done Surgical dentistry is a specialized area of dentistry that specializes in the surgical treatment of diseases of the oral cavity and maxillofacial region. This article covers modern diagnostics, operative treatment methods, surgical complications, and future prospects. The purpose of this article is to analyze the processes of surgical dentistry and study modern approaches.